ARMBRUSTERITE, K5Na6Mn3+ Mn142+[Si9O22]4(OH)10·4H2O, A NEW MN HYDROUS HETEROPHYLLOSILICATE FROM THE KHIBINY ALKALINE MASSIF, KOLA PENINSULA, RUSSIA - Yakovenchuk V.N.; Pakhomovsky Y.A.; Ivanyuk G.Yu.; Selivanova E.A.; Men'shikov Y.P.; Krivovichev S.V.; Britvin S.N. (My University, 2007)
Armbrusterite, ideally K5Na6Mn3+ Mn142+[Si9O22]4 (OH)10 4H2O, is a new silicate of potassium, sodium, and manganese found in a thin cancrinite-aegirine-microcline vein within urtite at Mt. Kukisvumchorr. The mineral occurs in intimate association with raite. Other associated minerals are lamprophyllite, mangan-neptunite, pectolite, vinogradovite, calcite, molybdenite, galena, sphalerite, and fluorite. Armbrusterite occurs as split, curved crystals and spherulites (≤2 mm diameter). The mineral is translucent (transparent in thin fragments), dark reddish-brown. It has vitreous luster and light-brown streak. Cleavage is perfect on (001) and the fracture is uneven. Mohs hardness is about 3.5. In transmitted light, the mineral is reddish-brown, with strong pleochroism: X = light yellowish-brown, Y and Z = dark reddish-brown; dispersion r > v, weak. Armbrusterite is biaxial (-): α = 1.532(2), β = 1.560(2), γ = 1.564(2) (for λ = 589 nm), 2V varies from 10° to 20°. Optical orientation: X is perpendicular to (001). The mean chemical composition determined by electron microprobe and the Penfield method (for H2O) is (wt%): Na2O 5.26, MgO 0.19, Al2O3 0.04, SiO2 56.02, K2O 6.13, CaO 0.26, TiO2 0.04, MnO 23.62, Mn2O3 2.07, FeO 0.65, ZnO 0.20, H2O 4.1, sum. 98.58. Empirical formula calculated on the basis of Si = 36 is K5.03Na6.55(Mn12.862+ Mn1.013+Fe0.352+ Mg0.18Ca0.18Zn0.09Al0.03 Ti0.02)∑=14.72[Si36O88] (OH)10.10 · 3.75 H2O. Armbrusterite is monoclinic, C2/m, a = 17.333(2), b = 23.539(3), c = 13.4895(17) Å, β = 115.069(9)°, V = 4985.4(11) Å3, Z = 2. The strongest X-ray powder-diffraction lines are [d in Å, (I), (hkl)]: 12.28 (100) (001), 4.10 (10) (003), 3.562 (10) (113, 261), 3.260 (18) (114), 3.117 (13) (203), 3.077 (54) (004), 2.622 (10) (371). The crystal structure of armbrusterite was refined to R1 = 0.085 on the basis of 3960 unique observed reflections. The structure is based upon double silicate [Si9O22] layers consisting of 5-, 6-, 7-, and 8-membered tetrahedra rings. The layers are linked via octahedral sheets formed by Na and Mn octahedra. The interior of the double silicate layers is occupied by K+ cations and H2O molecules. The mineral is named in honor of Thomas Armbruster (b. 1950; University of Berne) for his outstanding contribution to structural mineralogy and cryst allography, especially to the study of Mn-rich minerals.
Keywords: ARMBRUSTERITE; CRYSTAL STRUCTURE; KHIBINY MASSIF; KOLA PENINSULA; NEW MINERAL; SODIUM-POTASSIUM-MANGANESE SILICATE